Demonstration of Magneto-Impedance Sensor on Multilayer Coil [Ni80Fe20/Cu]N Result of Electro-Deposition - Nahrun, Ahmad Asrori; Wicaksono, B. Anggit; Ismail, Ismail; Nuryani, Nuryani; Purnama, Budi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2016)
Demonstration performance magneto - impedance sensor on the coil wire multilayer [ Ni80Fe20/Cu ]N electro - deposition results presented in this paper . At first multilayer [ Ni80Fe20/Cu ]N deposited on a Cu wire into a coil and then the sample is modified by the number of windings 2 and 4. The results of impedance measurements under the influence of the magnetic field shows that the magneto - impedance ratio increases with the increase in the number of windings. Magneto - impedance ratio changed from 15 % to 17.4% with a change in the number of windings of 2 to 4. The fact these results allegedly contributed their self-inductance value of this magnitude greater contribution to the increase in the number of windings.Keywords: Magneto - impedance sensor, electro-deposition , multilayer coils [Ni80Fe20/Cu]N